Beyond First-Line Immune Checkpoint Inhibitor Therapy in Patients With Hepatocellular Carcinoma - Sharma, Rohini; Motedayen Aval, Leila (Frontiers in Immunology, 2021)
Until recently, the treatment landscape for hepatocellular cancer (HCC) was dominated by tyrosine kinase inhibitors (TKIs) which offered an overall survival (OS) benefit of when used both in the first-and second-line compared to best supportive care. However, the has changed with the introduction of immune checkpoint inhibitors (ICIs) for the treatment of HCC with significant improvement in OS and progression free survival reported with atezolizumab and bevacizumab compared to sorafenib in the first-line setting. However, the response to ICIs is 20-30% and invariably patients will progress. What remains unclear is the therapeutics which should be used following ICI exposure. Extrapolating from the evidence base in renal cell carcinoma, subsequent therapy with TKIs offers both a response and survival benefit and are recommended by European guidelines. However, there are a number of novel therapies emerging that target mechanisms of ICI resistance that hold promise both in combination with ICI or as subsequent therapy. This paper will discuss the evidence for ICIs in HCC, the position of second-line therapies following ICIs and research strategies moving forward.